2019
DOI: 10.1002/adem.201900398
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cellular Shape‐Memory Ceramics via Gradient‐Controlled Freeze Casting

Abstract: Shape‐memory ceramics offer promise for applications like actuation and energy damping, due to their unique properties of high specific strength, high ductility, and inertness in harsh environments. To date, shape‐memory behavior in ceramics is limited to micro‐/submicro‐scale pillars and particles to circumvent the longstanding problem of transformation‐induced fracture which occurs readily in bulk polycrystalline specimens. The challenge, therefore, lies in the realization of shape‐memory properties in bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…With the slower freezing front velocity, one would advance to the left in the stability‐microstructure map in which cellular growth is expected (indicated by an orange arrow in Figure 4D). This is demonstrated by Zeng et al who observed cellular pores by decreasing the freezing front velocity at constant temperature gradient 19 . However, this could not be the sole factor for the formation of the cells because the sample frozen under 0.7 µm/s and 4.9 K/mm with conventional freezing still exhibits dendritic pores with a bimodal pore‐size distribution (Figure 4E).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…With the slower freezing front velocity, one would advance to the left in the stability‐microstructure map in which cellular growth is expected (indicated by an orange arrow in Figure 4D). This is demonstrated by Zeng et al who observed cellular pores by decreasing the freezing front velocity at constant temperature gradient 19 . However, this could not be the sole factor for the formation of the cells because the sample frozen under 0.7 µm/s and 4.9 K/mm with conventional freezing still exhibits dendritic pores with a bimodal pore‐size distribution (Figure 4E).…”
Section: Discussionmentioning
confidence: 75%
“…The polymer solution was degassed for 10 min to avoid air bubble formation during freezing. Directional freezing was conducted using a gradient‐controlled freeze‐casting setup 19 . The polymer solution was poured into a cylindrical mold placed on a thermoelectric plate.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, transition temperature is in the wide range that can be adjusted between 0 and 1200 C. [107] Apart from fine structure, Zeng et al presented a new method that aligns honeycomb-shaped cellular porous structure directionally to develop zirconia-based ceramics by gradient-controlled freezing casting. [108] In addition, the comparison of 1.5 and 2.0 mol% yttria stabilized zirconia between single crystal and polycrystalline structure has been analyzed by Crystal et al. [109] Owing to high ductility, high specific strength, and inertness in harsh environments, SMC is expected to offer promising solutions to the soft actuation applications.…”
Section: Shape Memory Ceramicsmentioning
confidence: 99%
“…In the past decade, the brittle nature of ZrO 2 has been mitigated by constructing miniature specimens (e.g., micro-/nano-pillars 8 , single/oligo-crystals 9 12 , nano-fibers 13 , 14 ), and structures formed thereof (e.g., honeycombs via 3D printing 15 , cellular foams via freeze casting 16 , 17 , and granular packings 3 , 18 ), where the ceramic is relatively free to expand/contract because of the high specific surface area and/or the removal of grain boundaries. Nevertheless, it remains a challenge to integrate these small-volume shape memory ceramics into a matrix material and realize their reversible phase transformation in a confined state without causing fracture.…”
Section: Introductionmentioning
confidence: 99%